Changes in the position of the medial meniscus owing to degenerative meniscus tears - Tomoyuki Kanayama; Yasushi Takata; Yoshihiro Ishida; Naoki Takemoto; Manase Nishimura; Satoru Demura; Junsuke Nakase (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
Background: While meniscal extrusion has been recognized as a key factor in meniscal dysfunction and osteoarthritis (OA) development, the specific movement of the posterior horn of the medial meniscus (MM) during extrusion, particularly in early-stage OA, remains unexplored. Therefore, in this study, we investigated the position of the MM in patients with medial knee pain and a Kellgren–Lawrence grade ≤1, investigating the relationship between meniscal extrusion and degenerative tears. We hypothesized that the MM extrusion (MME) would be larger when degenerative tears are present; the anterior horn would move posteriorly, and the posterior horn would move anteriorly, accordingly. Methods: A total of 181 knees (mean age 61.7 ± 12.1 years; 97 men and 84 women) were included. Simple radiographs were used to measure the weight-bearing line ratio and medial proximal tibia angle. Magnetic resonance imaging was used to measure the medial proximal tibia slope, medial meniscus extrusion, anterior and posterior horn position, and degenerative tears on the posterior segment of the medial meniscus. Those with degenerative tears were designated as group T and those without were designated as group C. Student's t-test and Pearson's χ2 test were performed to compare groups T and C. Statistical significance was set at p < 0.05. Results: Group T had a significantly larger medial posterior tibial slope (group T: 7.4 ± 2.3°; group C: 6.6 ± 2.2°, p = 0.010) and medial meniscus extrusion (group T: 2.7 ± 1.4 mm; group C: 1.9 ± 1.2 mm, p < 0.001) scores compared with group C. Furthermore, the posterior point of the anterior horn (group T: 16.3 ± 5.0 %; group C: 14.3 ± 3.8 %, p = 0.004) and anterior point of the posterior horn (group T: 36.4 ± 7.1 %; group C:26.9 ± 5.9 %, p < 0.001) were significantly larger in group T than in group C. Conclusion: Degenerative MM tears cause not only MME but also an anteroposterior shift.